Listening to early career teachers: how can elementary mathematics methods courses better prepare them to utilize standards-based practices in their classrooms? - Coester, Lee (Leila) Anne (Kansas State University, 2010)
This study was designed to gather input from early career elementary teachers with the goal of finding ways to improve elementary mathematics methods courses. Multiple areas were explored including the degree to which respondents’ elementary mathematics methods course focused on the NCTM Process Standards, the teachers’ current standards-based teaching practices, the degree to which various pedagogical strategies from mathematics methods courses prepared preservice teachers for the classroom, and early career teachers’ suggestions for improving methods courses. Both qualitative and quantitative methodologies were used in this survey study as questions were of both closed and open format. Data from closed-response questions were used to determine the frequency, central tendencies and variability in standards-based preparation and teaching practices of the early career teachers. Open-ended responses were analyzed to determine patterns and categories relating to the support of, or suggestions for improving, elementary mathematics methods courses. Though teachers did not report a wide variation in the incorporation of the NCTM Process Standards in their teaching practices, some differences were worth noting. Problem Solving appeared to be the most used with the least variability in its frequency of use. Reasoning, in general, appeared to be used the least frequently and with the most variability. Some aspects of Communication, Connections and Representation were widely used and some were used less frequently. From a choice of eight methods teaching practices, ‘Observing in actual classrooms or working with individual students’ and ‘Planning and teaching in actual classrooms’ were considered by early career teachers to be the most beneficial aspects of methods courses.
Keywords: Math methods; Elementary math methods; Early career teachers; Standards-based teaching; Preservice teachers; Elementary teacher preparation; Education, Curriculum and Instruction (0727); Education, Elementary (0524); Education, Mathematics (0280)